Inovasi Pemeliharaan Masal (Mass Rearing) Corcyra cephalonica (Lepidoptera : Pyralidae) untuk Pakan Alternatif Burung Walet Aerodramus fuciphagus (Apodiformis : Apodidae) - Damayanti, Nur; Ubaidillah, Rosichon; Priyono, Bambang; Rahayuningsih, Margareta (Universitas Negeri Semarang, 2023)
Swiftlets (Aerodramus fuciphagus) are small flying insectivorous birds and can make nests from their saliva. White swiftlets nests have very high economic value as food and are beneficial for health. Environmental factors are driving the emergence of feed innovation, namely mass rearing activities. The insects used in this study is the rice moth (Corcyra cephalonica). The purpose of this study is to analyze the innovation of mass rearing using bran, rice, and milled corn as feed media to influence the laying and life cycle of C. cephalonica. In this study using 3 feed media namely rice, bran, and milled corn using 4 treatments with different compositions 3 repetitions. The data analysis used in this study is a quantitative description. The data obtained were analyzed by statistical test Independent Sample t-Test. After being tested with statistically C. cephalonica egg production which had a significant difference, namely in treatments 2 (P2) with 3 (P3) and 4 (P4). The innovation of the feed media in treatment 2 had an effect on egg production, but the innovation of the three feed media had no effect on the life cycle of C. cephalonica, so the feed media that should be used as a feed innovation for Aerodramus fuciphagus is treatment 2, namely a combination of feed using corn (25%), bran (25%), and rice (50%) because they can produce more eggs than other treatments.